СЛУЧАЙ БОЛЕЗНИ ШАМБЕРГА У РЕБЕНКА С АТОПИЧЕСКИМ ДЕРМАТИТОМ - Налётов, Андрей Васильевич; Масюта, Дмитрий Иванович; Чалая, Любовь Феликсовна; Лянник, Виктория Александровна; Якимчук, Наталья Викторовна; Мацынина, Наталья Ивановна; Михеева, Александра Александровна (Медицина: теория и практика, 2020)